Isolation of Single-Domain Antibody Fragments That Preferentially Detect Intact (146S) Particles of Foot-and-Mouth Disease Virus for Use in Vaccine Quality Control - Harmsen, Michiel M.; Seago, Julian; Perez, Eva; Charleston, Bryan; Eblé, Phaedra L.; Dekker, Aldo (Frontiers in Immunology, 2017)
Intact (146S) foot-and-mouth disease virus (FMDVs) can dissociate into specific (12S) viral capsid degradation products. FMD vaccines normally consist of inactivated virions. Vaccine quality is dependent on 146S virus particles rather than 12S particles. We earlier isolated two llama single-domain antibody fragments (VHHs) that specifically recognize 146S particles of FMDV strain O1 Manisa and shown their potential use in quality control of FMD vaccines during manufacturing. These 146S-specific VHHs were specific for particular O serotype strains and did not bind strains from other FMDV serotypes. Here, we describe the isolation of 146S-specific VHHs against FMDV SAT2 and Asia 1 strains by phage display selection from llama immune libraries. VHHs that bind both 12S and 146S particles were readily isolated but VHHs that bind specifically to 146S particles could only be isolated by phage display selection using prior depletion for 12S particles. We obtained one 146S-specific VHH—M332F—that binds to strain Asia 1 Shamir and several VHHs that preferentially bind 146S particles of SAT2 strain SAU/2/00, from which we selected VHH M379F for further characterization. Both M332F and M379F did not bind FMDV strains from other serotypes. In a sandwich enzyme-linked immunosorbent assay (ELISA) employing unlabeled and biotinylated versions of the same VHH M332F showed high specificity for 146S particles but M379F showed lower 146S-specificity with some cross-reaction with 12S particles. These ELISAs could detect 146S particle concentrations as low as 2.3–4.6 µg/l. They can be used for FMD vaccine quality control and research and development, for example, to identify virion stabilizing excipients.